DETERMINAN PERKEMBANGAN ANAK PRASEKOLAH - Ridha, Ibda Linah Alf; Dewi, Vonny Khresna; Kristiana, Efi; Rusmilawaty, Rusmilawaty (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: Preschool children are a period where children really need attention in their developmental stages. Data from the Amuntai Selatan Health Center shows that preschool children who experience developmental disorders in 2024 are 0.71%. Several factors that affect child growth and development are knowledge factors, parenting patterns, and nutritional status. Objective: To find out the factors related to the growth and development of preschool children in the Amuntai Selatan Health Center work area in 2025. Method: This study was an observational analytical study with a cross-sectional approach. The sample used was purposive sampling with 91 preschool children. Data were analyzed using the Chi-Square test. Result: Six (6.6%) preschool children had questionable development. Fifteen (16.5%) mothers had insufficient knowledge. Twenty-six (28.6%) parents had an authoritarian parenting style. Twenty-eight (30.8%) children had poor nutritional status. Conclusion: There was a correlation between knowledge (P=0.035), parenting style (P=0.011), and nutritional status (P=0.015) and the development of preschool children at the Amuntai Selatan Community Health Center. Parents are encouraged to continue improving their knowledge of child growth and development by regularly taking their children to the Integrated Health Post.